Membangun Program Komunitas Wirausaha Siswa Melalui Pendidikan Berorientasi Kerja - Syamsuar Abbas; Zelhendri Zen; Reflianto Reflianto (Journal of Dedicators Community, 2019)
The community services purposes was to establish the work-oriented school community program and prepared the volunteers as trainer for digital design Corel draw and photoshop as well as the training of producing any souvenir made by shellfish shells in order to build a work-oriented education program in the Senior high school community and strengthen the students’ entrepreneur skills in two State Senior High School 12 and 13 Padang. This Community-Based Research approach involved two state senior high school students in Padang City. The result of the services showed that the program of community-based research plays an important role in realizing the work-oriented education program by strengthening the local industrial contents and extracurricular activities of entrepreneurship training in the schools. It could be seen from the improvement of students' skill in the creative business of digital design and souvenir products made by shellfish as well as increasing student’s spirit for directly involving in the activities of entrepreneurship in their school.  Follow up these activities should strengthen the cooperation among another school in West Sumatra to have the graduates of ready to work and ready to be entrepreneur indirectly help the government to reduce the educated unemployment in West Sumatra as well.